Cell cycle-specific action of nerve growth factor in PC12 cells: differentiation without proliferation. - Rudkin, B B (1989)
PC12 cells were manipulated in such a way as to permit the study of differentiation-specific responses independently from proliferative responses. Cells were starved for serum then exposed to nerve growth factor (NGF) or serum. Following addition of serum, cells incorporated thymidine in a synchronous manner. Subsequent to the wave of DNA synthesis, the cell number increased approximately two-fold. Addition of NGF to serum-starved cultures had no measurable effect on either parameter. Neurite outgrowth was more rapid and extensive and appearance of Na+ channels, measured as saxitoxin binding sites, more rapid than when NGF was added to exponentially-growing cells. Epidermal growth factor receptors were heterologously down-regulated by NGF with similar kinetics under both conditions. Induction of the proto-oncogene c-fos by NGF was also greater in the serum-starved cells than in exponentially-growing cultures. These results indicated that serum starvation resulted in synchronisation of the cultures and that NGF action may be cell cycle-specific. Analysis of the cellular response to NGF at different times during the cell cycle showed that c-fos was induced in the G1 phase but not in S or G2. Fluorescence-activated cell sorter analysis demonstrated that addition of NGF to exponentially-growing cells, resulted in their accumulation in a G1-like state. With regard to the study of the mechanism of NGF action, these results illustrate that measurements of NGF effects on specific components in the signal transduction pathway may be confounded by the use of exponentially-growing cultures.